Green Tea Catechin Normalizes the Enhanced Ca2+ Sensitivity of Myofilaments Regulated by a Hypertrophic Cardiomyopathy–Associated Mutation in Human Cardiac Troponin I (K206I). (December 2015) - Warren, Chad M.; Karam, Chehade N.; Wolska, Beata M.; Kobayashi, Tomoyoshi; de Tombe, Pieter P.; Arteaga, Grace M.; Bos, J. Martijn; Ackerman, Michael J.; Solaro, R. John
Abstract : Background—: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiovascular disease characterized by thickening of ventricular walls and decreased left ventricular chamber volume. The majority of HCM-associated mutations are found in genes encoding sarcomere proteins. Herein, we set out to functionally characterize a novel HCM-associated mutation (K206I-TNNI3) and elucidate the mechanism of dysfunction at the level of myofilament proteins. Methods and Results—: The male index case was diagnosed with HCM after an out-of-hospital cardiac arrest, which was followed by comprehensive clinical evaluation, transthoracic echocardiography, and clinical genetic testing. To determine molecular mechanism(s) of the mutant human cardiac troponin I (K206I), we tested the Ca 2+ dependence of thin filament–activated myosin-S1–ATPase activity in a reconstituted, regulated, actomyosin system comparing wild-type human troponin complex, 50% mix of K206I/wildtype, or 100% K206I. We also exchanged native troponin detergent extracted fibers with reconstituted troponin containing either wildtype or a 65% mix of K206I/wildtype and measured force generation. The Ca 2+ sensitivity of the myofilaments containing the K206I variant was significantly increased, and when treated with 20 µmol/L (-)-epigallocatechin gallate (green tea) was restored back to wild-type levels in ATPase and force measurements. The K206I mutation impairs the ability of the troponin I to inhibit ATPase activity in the absence of calcium-bound human cardiac troponin C. The ability of calcium-bound human cardiac troponin C to neutralize the inhibition of K206I was greater than with wild-type TnI. Conclusions—: Compromised interactions of K206I with actin and hcTnC may lead to impaired relaxation and HCM. Abstract : Supplemental Digital Content is available in the text.